(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the syntactic and semantic aspects of synonyms in English and Uzbek languages. Synonyms, which share similar or overlapping meanings, are analyzed to understand their grammatical roles and nuanced variations in meaning. The study highlights linguistic and cultural differences between the two languages, offering a comparative approach that benefits linguists, translators, and language learners. By examining the syntactic usage and semantic scope of synonyms, the article reveals how they function in communication and enrich language expression.